Multi-omics analyses were combined to construct ubiquitination-related features in colon adenocarcinoma and identify ASNS as a novel biomarker - Wang, Zhaohui; Zhang, Wenbing; Yin, Xin; Wu, Qinqing; Zhang, Yongwei; Qian, Yeben; Bao, Qian; Liu, Fubao (Frontiers in Immunology, 2024)
Background: As one of the malignant tumors with the highest incidence and fatality in the world, colon adenocarcinoma (COAD) has a very complex pathogenic mechanism, which has not yet been fully elucidated. Ubiquitin can regulate cell proliferation, cell cycle, apoptosis, DNA damage repair, and other processes by changing the activity of substrate proteins or causing ubiquitin-proteasome degradation. These are the key links in the pathogenesis of COAD, and ubiquitin plays an important role in the occurrence and development of COAD.We integrated transcriptomics, single-cell and clinical omics, and TCGA and GEO databases of COAD patient data. Cox and Lasso regression was employed to assess ubiquitination genes in COAD for generating ubiquitination-related features.The aim was to evaluate the prognostic value of these features for tumors and their impact on the immune microenvironment. At the same time, the expression level of model genes was further analyzed using single-cell data. Finally, the expression and function of ASNS, a key gene for this trait, were detected in vitro.Results: In our study, based on identifiable changes in the expression of marker genes, this feature can be used to classify patients with COAD. Kaplan-Meier survival analysis indicated that those with elevated risk scores in each cohort experienced inferior outcomes. There is good validation in both the training queue and the validation queue.The results of the immune infiltration analysis showed that the immune infiltration rate URGs Signature in COAD was significantly increased in the high-risk group. After the knockdown of ASNS, an important gene in the signature, the activity and migration capacity of SW620 and RKO cell lines and colony formation capacity were dramatically reduced in cell tests.We screened ubiquitination-related genes and constructed ubiquitinationrelated features, which can be used as reliable prognostic indicators of COAD. ASNS was identified as a possible biomarker for COAD.